Simplified synthesis of K2CO3-promoted hydrotalcite based on hydroxide-form precursors: Effect of Mg/Al/K2CO3 ratio on high-temperature CO2 sorption capacity - Jang, Hee Jin; Kim, Suji; Lee, Ki Bong (The Korean journal of chemical engineering, 2017)
Hydrotalcite was synthesized from hydroxide-form precursors to prepare a novel high-temperature CO 2 sorbent, and the effect of Mg/Al ratio on CO 2 sorption was studied. To enhance the CO 2 sorption capacity of the sorbent, K 2 CO 3 was coprecipitated during the synthetic reaction. X-ray diffraction analysis indicated that the prepared samples had a well-defined crystalline hydrotalcite structure, and confirmed that K 2 CO 3 was successfully coprecipitated in the samples. The morphology of the hydrotalcite was confirmed by scanning electron microscopy, and N 2 adsorption analysis was used to estimate its surface area and pore volume. In addition, thermogravimetric analysis was used to measure its CO 2 sorption capacity, and the results revealed that the Mg: Al: K 2 CO 3 ratio used in the preparation has an optimum value for maximum CO 2 sorption capacity.